Analysis of Microstructure and Mechanical Properties of Inconel 625 Alloy by Wire Arc Additive Manufacturing (WAAM) - K. Saravanakumar; V.G. Balaji; T. Srijha; V. Sanjay; K. Thatchuneswaran (Archives of Metallurgy and Materials)
An arc is used as a heat source in the manufacturing process known as wire arc additive manufacturing (WAAM), which uses layer-by-layer cladding to fuse wire. In the current work, Wire Arc Additive Manufacturing (WAAM)-fabricated Inconel 625 alloy has been examined. The research was done on the microstructure, mechanical characteristics, and impact of the solidification rate on the characteristics of the manufactured specimens for the Inconel 625 alloy. Microstructural analysis has shown that the specimen’s layers have varying microstructures. The bottom layer exhibits a blocky or equiaxed microstructure because of the faster solidification rate, while the upper zone generated elongated and discontinuous dendrites because of the slower solidification rate. This difference in the microstructure in the top and bottom zones directly influence the ultimate tensile strength, where the bottom zone has more tensile and yield strength than the top zone. Also, the presence of cracks in the top zone, which is found during the fractography test, also correlated the top zone’s ultimate tensile strength.